Okresowa analiza odchyleń w procesie budżetowania w przedsiębiorstwach przemysłu spożywczego - Rumniak, Paweł (Temporary Analysis of Distortion in the Process of Budgeting in Enterprises of Food Industry, 2005)
The article presents basic information about measuring and analyzing differences between a budget and data taken from the financial accounting system. There is not only information about differences but also about specific factors that cause those distortions
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 349-358